Project-based learning in Physics education: a bibliometric review - Muhamad Mi'da Farkhan; Heru Kuswanto; Yusman Wiyatmo (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
Project-Based Learning (PjBL) has been recognized as an effective instructional approach for enhancing conceptual understanding and 21st-century skills in physics education. However, there is a lack of systematic bibliometric studies that map the development, trends, and research gaps in this topic. This study aims to identify research areas that have been extensively explored, as well as those that remain underexplored within PjBL in Physics Education. The method employed is descriptive with bibliometric analysis using data from Scopus, through the stages of identification, screening, eligibility, and inclusion. The analysis was conducted using Publish or Perish (PoP) and VOSviewer software. From the 48 publications analyzed, it was found that the number of publications declined over the past three years, after peaking in 2021 due to the growing demand for 21st-century competency-based curricula. This decline is suspected to be related to implementation challenges during the COVID-19 pandemic. The distribution of affiliations and countries indicates that there are still institutions and nations not actively involved in this topic. Emerging research focuses, such as links to curriculum, scientific inquiry, and technology, present opportunities for further studies. The findings of this study highlight the need for expanding and deepening PjBL research in Physics Education across various national and institutional contexts.